Membaca Teks Mazmur 137:1-9 dari Perspektif Logoterapi Viktor Frankl - Irnawati Satigi (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
Abstract. Psalm 137:1-9 is a Hebrew poem depicting the psychological dynamics of the exiled people. Reading the text of Psalm 137:1-9 through the lens of Viktor Emil Frankl's logotherapy, within the Asian contextual hermeneutic framework employed in this paper, has opened up opportunities for other interpretations of the text. From a logotherapeutic perspective, the exile and the destruction of the temple and Jerusalem placed them in a state of noödinamika. Rather than hindering spiritual growth, this painful reality can be used as a gateway to other interpretations of the dynamics of the relationship between the people and their God. Through a logotherapeutic perspective, Psalm 137:1-9 is understood as a portrait of the spiritual transformation of the people in response to their situation and condition.Abstrak. Mazmur 137:1-9 merupakan puisi Ibrani yang berisi dinamika psikologis umat di pembuangan. Pembacaan teks Mazmur 137:1-9 dengan menggunakan lensa logoterapi dari Viktor Emil Frankl, dalam kerangka kerja hermeneutik kontekstual Asia yang dikerjakan dalam tulisan ini telah membuka peluang pemaknaan yang lain terhadap teks. Dari kacamata logoterapi, peristiwa pembuangan dan momentum kehancuran bait suci serta kota Yerusalem telah menempatkan mereka dalam kondisi noödinamika. Alih-alih menjadi penghambat pertumbuhan spiritual, realita yang menyakitkan dapat dijadikan gerbang menuju pemaknaan yang lain tentang dinamika hubungan umat dan Tuhannya. Melalui perspektif logoterapi, Mazmur 137:1-9 dipahami sebagai sebuah potret transformasi spiritual umat dalam merespon situasi dan kondisinya.